Formation mechanism of the quarantine hotel booking intention of potential consumers - Wu, Guihua; Wang, Yanwen; Li, Xuejia; Lin, Meizhen (Frontiers in Psychology, 2022)
In this paper, we investigated the quarantine hotel (QH) booking intention (BI) of potential consumers from a corporate social responsibility (CSR) perspective. Mixed methods were adopted to explore the formation mechanisms of QH BI of potential consumers when the COVID-19 pandemic recedes. In Study 1, we constructed a theoretical model of QH BI of potential consumers based on grounded theory and put forward research propositions. In Study 2, we tested the robustness of the model and identified the mediating effect through two situational experiments. The research results showed that: (1) Potential customers are more willing to book QHs than normal hotels (NHs). (2) Multiple mediating mechanisms are involved in the effect of the operation as a quarantine facility on BI of potential consumers, including “QH-corporate social responsibility (CSR)-customer trust (CT)-BI” and “QH-CSR-customer gratitude (CG)-BI”. This research not only has theoretical significance for deepening and expanding social exchange theory and hotel CSR theories but also provides guidance for the participation of the hotel industry in the prevention and control of the COVID-19 pandemic and hotel marketing after the pandemic ends.